Strategi Adaptasi Radio Siaran Konvensional dalam Menghadapi Disrupsi Podcast dan Platform Audio Digital: Studi Kasus Radio Swasta di Era Post-Pandemi - Edison Edison; Muhammad Zacky Mahendra (Lembaga Yasin AlSys, 2026)
The conventional broadcast radio industry in Indonesia is facing increasingly intense disruption pressures due to the emergence of podcasts and digital audio platforms that have fundamentally changed audiences’ media consumption patterns. The Covid-19 pandemic also accelerated this shift, prompting private radio stations to formulate comprehensive adaptation strategies to maintain their existence and relevance. This study aims to analyze the adaptation strategies of conventional broadcast radio in facing the disruption of podcasts and digital audio platforms in the post-pandemic era. This study used a qualitative approach with a case study design. Data were collected through in-depth discussions with key informants consisting of a program director, senior producer, head of the digital division, marketing manager, and senior broadcaster, and were strengthened through field observation and documentation study. The data were analyzed using the Miles and Huberman interactive model. The results identified five main dimensions of adaptation strategies, namely the transformation of content distribution toward multiplatform delivery, the development of original podcasts with a strong identity, the repositioning of live broadcasting as a differentiation value, the transformation of human resource competencies, and the restructuring of revenue models. The conclusion of this study affirms that conventional radio is not heading toward extinction but is undergoing a process of mediamorphosis that, if managed strategically, can produce an audio medium that is more adaptive, competitive, and relevant in the digital era. The implications of this study contribute to the development of media adaptation studies and provide practical input for the radio industry in designing sustainable digital transformation strategies.